LIVING QUR’AN TRADISI ISLAM NUSANTARA: KAJIAN TERHADAP TRADISI PELET BETTENG PADA MASYARAKAT PROBOLINGGO - Musolli, Musolli; Zayyadi, Ach; Maziya, Ika (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2021)
This thinking is based on a phenomenon that develops and thrives in the people of Probolinggo Regency, where every woman who is pregnant and enters a particular month must be prayed for through the rokat pelet betting activity. This study aims to understand the Rokat Pellet betting tradition that occurs in the people of Probolinggo Regency from the perspective of the living Qur'an. This research uses a qualitative with phenomenology, a research procedure that produces descriptive data in written or spoken words from the people observed. The results showed that the tradition of rokat pellet betting produced a persuasive-cultural approach model to sow Islam to the community. The tradition of rokat pelet betting is a phenomenon of the living Qur'an for four reasons; first, as a form of gratitude for personal piety; second, as a medium to strengthen ukhuwah and silaturrahmi (brotherhood and affection); third, as a symbol of the request for safety to the unborn baby; fourth, as a syi'ar media based on the culture of the archipelago.